Distorted copper(ii) radicals with sterically hindered salens: electronic structure and aerobic oxidation of alcohols. Issue 37 (10th September 2020) - Kunert, R.; Philouze, C.; Berthiol, F.; Jarjayes, O.; Storr, T.; Thomas, F.
Abstract : Strongly distorted copper salen complexes show a unique stability in four different redox states by CV. Copper phenoxyl radical complexes are structurally characterized. They promote the catalytic aerobic oxidation of 2-phenylethanol under air. Abstract : The sterically hindered salen ligands featuring biphenyl and tetramethyl putrescine linkers were synthesized and chelated to copper. The resulting complexes CuL bp, t Bu, CuL bp, OMe, CuL pu, t Bu and CuL pu, OMe were structurally characterized, showing a significanty tetrahedrally distorted metal center. The complexes show two reversible oxidation waves in the range 0.2 to 0.8 V vs . Fc + /Fc. A further reduction wave is detected in the range −1.4 to −1.7 V vs. Fc + /Fc. It is reversible for CuL bp, t Bu and CuL bp, OMe and assigned to the Cu II /Cu I redox couple. One-electron oxidation of CuL bp, OMe, CuL pu, t Bu and CuL pu, OMe was performed chemically and electrochemically. It is accompanied by a quenching of the EPR resonances. Phenoxyl radical formation was established by X-Ray diffraction on the cations [CuL bp, OMe ] + and [CuL pu, OMe ] +, whereby the coordination sphere is elongated upon oxidation with quinoidal distributions of bond distances. The cations exhibit a NIR band of moderate intensity in their optical spectrum, supporting their classification as class II mixed-valent radical species according to the Robin Day classification. The proposed electronic structures are supported by DFT calculations. The cations [CuL bp, OMe ] +, [CuL pu, t Bu ] + and [CuL pu, OMe ] + were active towards aerobic oxidation of the unactivated alcohol 2-phenylethanol, with TON numbers up to 58 within 3 h.